138 THE MULTITARGETED RECEPTOR TYROSINE KINASE INHIBITOR ABT-869 INDUCES APOPTOSIS IN BAF3 CELLS EXPRESSING THE FLT3 INTERNAL TANDEM DUPLICATION MUTATION. (1st January 2006) - Parcells, B. W.; Ikeda, A. K.; Moore, T. B.; Glaser, K. B.; Sakamoto, K. M.
Abstract : Purpose of Study: Constitutive activation of the FMS-tyrosine kinase 3 (FLT3) receptor has been identified as the most frequent genetic abnormality in acute myeloid leukemia (AML) and also confers a poor prognosis. FLT3 receptor signaling is deregulated due to internal tandem duplications (ITD) in the juxtamembrane domain or point mutations in the activation loop of the kinase domain (TKD. ABT-869 is a novel multitargeted small-molecule inhibitor of receptor tyrosine kinases in the type III subfamily that includes FLT3, c-FMS, c-KIT, and all VEGF and PDGF receptors. ABT-869 inhibits the growth of a human myeloid leukemia cell line MV-411 that expresses the FLT3-ITD mutation both in vitro and in vivo. To determine the effects of ABT-869 on other mutant FLT3-expressing cell lines, we treated murine lymphoid BaF3 cells stably expressing FLT3-ITD or FLT3-D835V and wild-type Baf3 cells at varying concentrations of the drug. Methods: The viability of BaF3 cells treated with ABT-869 at concentrations ranging from 1 pM to 10 μM was determined using trypan-blue exclusion method. The effect of ABT-869 on apoptosis was examined using annexin V-FITC or propidium iodide staining and FACs analysis. The effect of ABT-869 on subcutaneous tumors in SCID mice was examined by injecting 5 × 10 6 of FLT3-ITD, FLT3-D835V, or wild-type cells ( n = 15/group). Tumor growth was measured by vernier caliper. Three weeks after inoculation, mice received daily oral doses of vehicle or ABT-869 (20 mg/kg or 40 mg/kg). Results: ABT-869 inhibited the growth of FLT3-ITD-expressing cells at an IC50 of 10 nM and of FLT3-D835V cells at an IC50 of 100 nM. Growth of wild-type BaF3 cells was inhibited by ABT-869 at an IC50 of 10 μM. Apoptosis was observed in BaF3 cells expressing FLT3-ITD 24 hours after ABT-869 treatment at a concentration of 10 nM but not in BaF3-D835V or wild-type cells. Preliminary in vivo data suggest that ABT-869 induced significant tumor regression in FLT3-ITD-injected mice and increased survival. ABT-869 did not significantly affect tumor growth or survival in FLT3-D835V or wild-type injected mice. Conclusions: Baf3 cells expressing the FLT3-ITD are more susceptible to the proapoptotic effects of ABT-869 compared to cells expressing the D835V mutation or wild-type cells. Our results suggest that ABT-869 may be effective in AML patients who have blasts harboring the FLT3-ITD mutation.